ANALISIS SALURAN PEMASARAN DAN TRANSMISI HARGA TANDAN BUAH SEGAR (TBS) KELAPA SAWIT PADA PETANI SWADAYA DI DESA SARI GALUH KECAMATAN TAPUN KABUPATEN KAMPAR - Ermi Tety; Evy Maharani; Selviana Deswita (Program Studi Pendidikan Ekonomi Universitas Riau, 2013)
The purpose of this research is to find out and analyze: channels and marketingmargins of TBS as well as palm oil prices received by Swadaya Farmers; thecorrelation or relationship between the price of oil palm paid PKS with the pricereceived by swadaya farmers and the effect of price (price transmission elasticity)from oil palm at PKS with the price recevied by swadaya farmers at sari galuhvillage, tapung district, kampar subdistrict. This research was conducted from March2012 to August 2012. The method that the reasearch used was survey method. Thesample take used by purposive sampling. The sampling of the reaserch was 42swadaya farmers with the age of palm trees between 8-12 years, whereas fortraders and pks used by method snowball sampling by following marketing chanel.The results of this research show only one market by channel from swadaya farmerstbs, from farmer to traders than to PKS and marketing margins used the periodictime series data from January to December 2011 Rp. 223,12. The price thatreceived by farmer is 85,05%. The correlation value of the price from swadayafarmers with the price PKS was 0,983. The value of the elasticity of pricetransmission between the price received from swadaya farmers and the price of oilpalm by PKS was 0,085.Keywords: Marketing channels, margins, price transmission, swadaya farmers.